Primordial black hole constraints with Hawking radiation—A review - Auffinger, Jérémy (Progress in particle and nuclear physics, 2023)
Primordial black holes are under intense scrutiny since the detection of gravitational waves from mergers of Solar-mass black holes in 2015. More recently, the development of numerical tools and the precision observational data have rekindled the effort to constrain the black hole abundance in the lower mass range, that is M<1023g. In particular, primordial black holes of asteroid mass M∼1017–1023g may represent 100% of dark matter. While the microlensing and stellar disruption constraints on their abundance are weaker than originally proposed, Hawking radiation of these black holes seems to be the primary method for detecting or constraining such black holes. Hawking radiation constraints on primordial black holes date back to the first papers by Hawking. Black holes evaporating in the early universe may have generated the baryon asymmetry, modified Big Bang nucleosynthesis, distorted the cosmic microwave background and/or produced cosmological backgrounds of stable particles such as photons and neutrinos. At the end of their lifetime, exploding primordial black holes would produce high energy cosmic rays that would provide invaluable access to the physics at energies up to the Planck scale. In this review, we describe the main principles of Hawking radiation, which lie at the intersection of general relativity, quantum mechanics and statistical physics/thermodynamics. We then present an up-to-date status of the different constraints on primordial black holes that rely on the evaporation phenomenon, and give, where relevant, prospects for future work. In particular, we also discuss non-standard black holes and the emission of Beyond the Standard Model degrees of freedom.